Cationic amphiphilic microfibrillated cellulose (MFC) for potential use for bile acid sorption. (5th November 2015) - Zhu, Xuhai; Wen, Yangbing; Cheng, Dong; Li, Changmo; An, Xingye; Ni, Yonghao
Highlights: Cationic amphiphilic MFC with different chemical structures is synthesized. Increasing charge density increases the sorption capacity of CMFC. Increasing alkyl length increases the sorption capacity of the modified CMFC. Sorption behavior of the modified CMFC is less influenced by the ionic strength. Sorption capacity of the modified MFC is higher for deoxycholate than cholate. Abstract: In this work, Micro-fibrillated Cellulose (MFC) was cationically modified by quaternary ammonium groups with different chemical structures aiming to improve the sorption capacity to bile acid. The in-vitro bile acid sorption was performed by investigating various factors, such as quaternary ammonium group content and length of its alkyl substituent of the modified cationic MFC (CMFC), ionic strength, initial concentration and hydrophobicity of bile acid. The results showed that the sorption behavior of the modified CMFC was strongly influenced by the quaternary ammonium group content and the lengths of its alkyl substituent, the sorption capacity for the modified CMFC with a C18 alkyl substituent, was approximately 50% of that of Cholestyramine. The experimental isotherm results were well fitted into the Temkin model. The effect of salts in the solution was smaller for the bile acid sorption onto the hydrophobic CMFC than the CMFC. It was also found that the binding capacity of CMFC was higher for more hydrophobic deoxycholate in comparison with cholate.